The Cutting-edge of CRISPR for Cancer Treatment and its Future Prospects - Liau, Kah M.; Ooi, An Gie; Mah, Chian Huey; Yong, Penny; Kee, Ling Siik; Loo, Cheng Ze; Tay, Ming Yu; Foo, Jhi Biau; Hamzah, Sharina (Current Pharmaceutical Biotechnology, 2024)
CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats) is a versatile technology that allows precise modification of genes. One of its most promising applications is in cancer treatment. By targeting and editing specific genes involved in cancer development and progression, CRISPR has the potential to become a powerful tool in the fight against cancer. This review aims to assess the recent progress in CRISPR technology for cancer research and to examine the obstacles and potential strategies to address them. The two most commonly used CRISPR systems for gene editing are CRISPR/Cas9 and CRISPR/Cas12a. CRISPR/Cas9 employs different repairing systems, including homologous recombination (HR) and nonhomologous end joining (NHEJ), to introduce precise modifications to the target genes. However, off-target effects and low editing efficiency are some of the main challenges associated with this technology. To overcome these issues, researchers are exploring new delivery methods and developing CRISPR/Cas systems with improved specificity. Moreover, there are ethical concerns surrounding using CRISPR in gene editing, including the potential for unintended consequences and the creation of genetically modified organisms. It is important to address these issues through rigorous testing and strict regulations. Despite these challenges, the potential benefits of CRISPR in cancer therapy cannot be overlooked. By introducing precise modifications to cancer cells, CRISPR could offer a targeted and effective treatment option for patients with different types of cancer. Further investigation and development of CRISPR technology are necessary to overcome the existing challenges and harness its full potential in cancer therapy.
Keywords: delivery methods